2012
DOI: 10.1016/j.neuron.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Rhythms: A Synergistic View of Frequency and Temporal Coding in Neuronal Networks

Abstract: In the CNS, activity of individual neurons has a small but quantifiable relationship to sensory representations and motor outputs. Coactivation of a few 10s to 100s of neurons can code sensory inputs and behavioral task performance within psychophysical limits. However, in a sea of sensory inputs and demand for complex motor outputs how is the activity of such small subpopulations of neurons organized? Two theories dominate in this respect: increases in spike rate (rate coding) and sharpening of the coincidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
131
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 126 publications
2
131
1
Order By: Relevance
“…Indeed, several studies probing the relation of population performance with population size reported that population information grows steadily with population size. This led to the hypothesis that in sufficiently large ensembles each neuron contributes independently to a population code (Gawne et al, 1996;Rolls et al, 1997;Reich et al, 2001;Quiroga et al, 2007) and that large populations may encode very high amounts of information (Abbott et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies probing the relation of population performance with population size reported that population information grows steadily with population size. This led to the hypothesis that in sufficiently large ensembles each neuron contributes independently to a population code (Gawne et al, 1996;Rolls et al, 1997;Reich et al, 2001;Quiroga et al, 2007) and that large populations may encode very high amounts of information (Abbott et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A sensory system can employ multiple types of codes (Ainsworth et al, 2012). For instance, the barn owl auditory system computes two sound localization cues, using a rate code for interaural level differences and a temporal code for interaural timing differences (Konishi, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The first pool is the readily releasable pool (RRP) and the other is the recycling pool (RP) (15), modeled with mass-action kinetics. Synaptic dynamics has been repeatedly used to describe changes in spike rates in neural network populations (16) and emergence of gamma oscillations (17). Furthermore network connectivity can also participate to define bursting or the oscillation frequency in neural networks (18,19).…”
mentioning
confidence: 99%